(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2014)
Wireless sensor networks (WSNs) are exposed and being attacked by opponents as they are randomly deployed in open environments. Opponents can extract confidential information like secret keys by inserting their own nodes as compromised nodes and uses them to introduce various security attacks. So detection of such nodes is being the major issue to be addressed. In this paper we present Compro-Moto â€“ as an efficient intrusion detection system to detect compromised nodes in WSNs. Simulation results clearly shows the benefits of Compro-Moto :(i). It is not sensitive to any kind of security attacks (ii).It endows detection range up to 99.99%. (iii)It endows false detection rate less than 1%in WSNs.(iv).It endows less total overhead and less packet loss rate. These benefits are the Â achievement of Compro-Moto system that requires little memory and less communication overhead and also it can scale up to millions of nodes.